Coordinated planning of the production program of enterprises business network - Khadzhynova, O. (Економічний вісник Донбасу, 2016)
The article deals with the model of production planning activities of enterprises business network and the methodology of constructing a coherent planning system. Using the coordinated planning model of production activities allows to solve the following problems consistently and iteratively: basic coordinated production planning provided the demand is known; optimum planning, taking into account casual external demand, the results of which are deterministic input parameters for the first task; optimization of the system viability of enterprises business network by controlling domestic product prices, the results of which are inputs to the second problem. The author suggests a scientific and methodical approach to the coordinated planning of production enterprises business network, which is a complex of economic and mathematical models. У статті розглянуто моделі планування виробничої діяльності підприємств підприємницької мережі і методологія побудови системи узгодженого планування. Використання моделі узгодженого планування виробничої діяльності дозволяє послідовно й ітеративно вирішувати такі завдання: базове узгоджене планування випуску продукції в умовах, коли попит відомий; оптимальне планування, що враховує випадковість зовнішнього попиту, результати якого є вхідними детермінованими параметрами для завдання першого; оптимізація системного критерію життєздатності підприємств підприємницької мережі шляхом регулювання внутрішніх цін на продукцію, результати якого є вхідними параметрами для завдання другого.Автором запропоновано науково-методичний підхід до узгодженого планування виробництва підприємств підприємницької мережі, який являє собою комплекс економіко-математичних моделей. В статье рассмотрены модели планирования производственной деятельности предприятий предпринимательской сети и методология построения системы согласованного планирования. Использование модели согласованного планирования производственной деятельности позволяет последовательно и итеративно решать следующие задачи: базовое согласованное планирование выпуска продукции в условиях, когда спрос известен; оптимальное планирование, учитывающее случайность внешнего спроса, результаты которого являются входными детерминированными параметрами для задачи первой; оптимизация системного критерия жизнеспособности предприятий предпринимательской сети путем регулирования внутренних цен на продукцию, результаты которого являются входными параметрами для задачи второй.Автором предложен научно-методический подход к согласованному планированию производства предприятий предпринимательской сети, который представляет собой комплекс экономико-математических моделей.